(untitled) (Pesquisa Odontológica Brasileira, 2000)
Panoramic radiographic methods provide images which present distortions of bilateral anatomical structures of the face as well as magnification. Currently, panoramic radiographs have been used to analyze vertical, horizontal and angular measurements. In an attempt to evaluate the presence of symmetry in the bilateral images of the mandibular rami, both their area and perimeter were obtained from panoramic radiographs of 8- to 10-year old children. The contour of the images of both rami was divided at the gonial angle and at the deeper point of the anterior border and it was transferred to translucent tracing paper and then to a computer through a scanner apparatus. The images were measured using a scan software and the values obtained were analyzed. The results showed that there was symmetry in both area and perimeter measurements, in male and female children.